Patterns and Barriers of Physical Activity among Medical Students in Davangere, Karnataka - Vidya V Patil; Vidya Basavaraju (Medsci Publications, 2020)
Introduction: Physical inactivity has been identified as the fourth leading risk factor for global mortality Medical students play an important role in promoting health education to the patients starting with their clinical training years. Objectives: The study was conducted to assess the patterns of physical activity among the medical students and to assess the perceived barriers of physical activity among them. Methodology: A cross sectional study was conducted among students of a medical college those students available at the time of interview were included in the study. The study was conducted from 19/10/2019 to 2/12/19. A batch of interns who were posted to community medicine department, were trained with the Global Physical Activity Questionnaire and were asked to collect the data from other medical students. Results: Out of the 250 students interviewed, 46% of them were males and 54% of them were females. Around 76% of the male students and 85% of the female students does not fulfil the WHO recommendations on moderate physical activity on health. Based on MET minutes/week ≥ 67% of the students are inactive/low active, 33% are active. Conclusion: Majority of medical students have not met the recommended WHO criteria for physical activity among students.